A Dynamical Model of Kinesin-Microtubule Motility Assays - Gibbons, Frank (2001)
A two-dimensional stochastic model for the dynamics of microtubules in gliding-assay experiments is presented here, which includes the viscous drag acting on the moving fiber and the interaction with the kinesins. For this purpose, we model kinesin as a spring, and explicitly use parameter values to characterize the model from experimental data. We numerically compute the mean attachment lifetimes of all motors, the total force exerted on the microtubules at all times, the effects of a distribution in the motor speeds, and also the mean velocity of a microtubule in a gliding assay. We find quantitative agreement with the results of J. Howard, A. J. Hudspeth, and R. D. Vale, Nature. 342:154–158. We perform additional numerical analysis of the individual motors, and show how cancellation of the forces exerted by the many motors creates a resultant longitudinal force much smaller than the maximum force that could be exerted by a single motor. We also examine the effects of inhomogeneities in the motor-speeds. Finally, we present a simple theoretical model for microtubules dynamics in gliding assays. We show that the model can be analytically solved in the limit of few motors attached to the microtubule and in the opposite limit of high motor density. We find that the speed of the microtubule goes like the mean speed of the motors in good quantitative agreement with the experimental and numerical results.